The British naval staff in the First World War - Black, Nicholas (Boydell Press, 2009)
Nicholas Black examines the role of the Naval Staff of the Admiralty in the 1914-18 war, reassessing both the calibre of the Staff and the function and structure of the Staff. He challenges historians such as Arthur Marder and naval figures such as Captai.
Keywords: Great Britain. -- Royal Navy -- History -- World War, 1914-1918.; Great Britain. -- Royal Navy; World War, 1914-1918 -- Naval operations, British.; Sailors -- Great Britain.; Marins -- Grande-Bretagne.; HISTORY -- Military -- World War I.; HISTORY -- Modern -- General.; Sailors; Great Britain; Marine; Weltkrieg -- 1914-1918; Großbritannien; GroÃ#x9F; britannien.; 1914-1918; Admiralty.; Anderson Medal.; British Naval Staff.; Dardanelles Operation.; Economic Blockade.; First World War.; Geddes.; Grand Fleet.; Jellicoe.; Naval Operations.; Naval Staff.; Strategy.; U-boat War.; U-boat Warfare.; History